Waktu Pemberian Asam Humat Tanah Gambut Kalimantan Sebagai Antiinflamasi Telapak Kaki Mencit Yang Diinduksi Karaginan - Mukarlina, Rusliandi, Diah Wulandari R. (Universitas Tanjungpura, 2017)
Peat soil is a land that is widely found on the Borneo Island. Approximately 75% of peat soil consists of soil organic matter, and 75% of soil organic matter consists of humus compounds. The purpose of this research is to know the volume of induction of lambda carrageen which can cause udem and to know the best time of giving humic acid before induction of carrageen. The study used a mice Swiss strain weighing 25-30 grams and 3 months old. The study used Randomized Block Design with treatment of humic acid 30 minutes before induction of carrageen, humic acid administration 60 minutes before induction of carrageen, humic acid administration 90 minutes before induction of carrageen and negative control. The results show that the best 1% lambda carrageen induction volume was 0.15 ml because it can cause udem in the test animal of 39.2 mm3. Best treatment of humic acid is found in the administration of humic acid 30 minutes before induction of carrageen. The highest inhibition of udem occurred in the 180th minute by 30.8%.